IndiGen project and its application in criminal law in India - Abhinav Vardhan Sharma; Somdutt Bhardwaj (Wolters Kluwer Medknow Publications, 2023)
India has more than 4500 distinct population which are different based on caste, tribe, religion, locations, physical features, social beliefs, and language. Genome India project was approved in February 2020 by the Ministry of Science and Technology to aim gene-mapping of 10,000 samples across India. The IndiGen program achieved the entire genome sequencing of the 1029 healthy Indians. Gene sequencing at population scale can now be benchmarked using this method. The ability to decode the genetic blueprint of Indians for diagnosis and treatment of rare diseases will be emerged further on. A national of different deoxyribonucleic acids (DNAs) is maintained by the government for the purpose of medical and matching the criminal DNAs during trials. The UK established its National DNA Database in 1995 by the name of National DNA Database. Australia has almost 8.37 million DNA profiles, which they are using as forensic data. It involves novel methods for monitoring and controlling behavior as well as redesigned means of administering justice, all of which contribute to the construction of new ideas of justice and social governance. DNA phenotyping can be included in the criminal justice system by the project to make it DNA database and DNA databank for the law. This goal can be accomplished by determining the distribution of the data of the genetic outlines by geographical zone and the following closeness of the reference sample to a probable area of origin.